2022
DOI: 10.1002/aelm.202200421
|View full text |Cite
|
Sign up to set email alerts
|

Second‐Order Memristor Based on All‐Oxide Multiferroic Tunnel Junction for Biorealistic Emulation of Synapses

Abstract: The brain has the ability to learn and evaluate as it receives and registers information. Signals between neurons are transmitted via synapses whose plasticity is modulated by usage. A bio-realistic electrical analog is a secondorder memristor, where the short-term internal dynamics influence the longterm state. It is achieved here with an all-oxide multiferroic tunnel junction: La 0.7 Sr 0.3 MnO 3 / BaTiO 3 / La 0.7 Sr 0.3 MnO 3 . Similar to the modulation of synaptic weight by stimuli, multi-levels of resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Similar to the short‐term memory of the human brain, we demonstrated that the shorter the learning interval of the device, the better remembered what is to be learnt. [ 78–80 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the short‐term memory of the human brain, we demonstrated that the shorter the learning interval of the device, the better remembered what is to be learnt. [ 78–80 ]…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the short-term memory of the human brain, we demonstrated that the shorter the learning interval of the device, the better remembered what is to be learnt. [78][79][80] Finally, using the device as a physical reservoir, we implemented reservoir computing, which is a computing architecture for the efficient processing of sequential and temporal inputs based on the biological nervous system. [71,72,81,82] Reservoir computing includes a reservoir (which receives input and transforms it high dimensionally) and a readout (which is used for training), as shown in Figure 9a.…”
Section: Resultsmentioning
confidence: 99%
“…In neuroscience, spike-rate-dependent plasticity (SRDP) is another essential synaptic function for modifications of memory learning processes that describes the synaptic plasticity dependency on the spike frequency [ 36 , 37 , 38 , 39 ]. Figure 5 a illustrates the frequency-dependent EPSC response ranges from 5 Hz to 100 Hz with an amplitude of +0.85 V/200 µs in the short-term memory (STM) mode.…”
Section: Resultsmentioning
confidence: 99%
“…The postsynaptic currents increase (learning process) due to the spike train frequency of 5 Hz and 10 Hz at the first stage, whereas at the second stage at spike train frequency of 2 Hz, the current increment or even decreasing trends (forgetting process) were observed. So, the potentiation and depression of synaptic weights are controlled by the pulse train frequency without the application of opposite polarity voltage, which mimics a bio-synapse [ 37 , 38 ]. Similar behavior was reported by Khanas et al and Yan et al previously [ 38 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation